Meningkatkan Produktivitas Budidaya Hidroponik di Lahan Terbatas Menggunakan Metode PDCA - Elsa Amanda Putri; Olif Aulia; Nabila Dwi Isa Melandari; Jessica Mayddy Amanda; Amanda Dian Rahmawati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
17 August 1945, University Surabaya has expanded its limited green space and educated students and the community about plant development without planting material, or it is referred to as contemporary farming by using the rooftop area on the third level of the Engineering Building (Q) for hydroponic plant cultivation. Using the PDCA (Plan, Do, Check, Action) method, one may improve the productivity of plants in hydroponic farming. The NFT (Nutrient Film Technique) system, which consists of three pipes stacked in parallel places, is used in the design of the hydroponic growing system. Rockwool, flannel cloth, plastic cups, nutrients, and a pH or TDS (Total Dissolved Solid) measuring device are among the equipment and supplies utilized. Choosing plants that can be used on small amounts of land are.